2021
DOI: 10.3389/fpubh.2021.730845
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence and Associated Factors in Patients With Type 2 Diabetes: A Structural Equation Model

Abstract: Background: The number of patients with type 2 diabetes (T2D) is increasing. Medication treatment is of great importance to stabilize blood glucose. Previous studies have reported that neuroticism, self-efficacy, and social support are factors associated with medication adherence, but few studies have fully investigated the mechanisms between these factors and medication adherence in patients with T2D.Purpose: To explore the prevalence of medication adherence and the factors associated with medication adherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Previous systematic reviews have reported different risk factors for non-adherence due to differences in the definition of target diseases and therapeutic medications. 12 , 16 , 18 , 25 Age, sex, dementia, and presence of a roommate have been reported as risk factors for non-adherence. 12 , 18 , 21 In our study, we newly analyzed the number of medications to be discontinued before surgery and the number of days between the pharmacist interview and surgery as risk factors for non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews have reported different risk factors for non-adherence due to differences in the definition of target diseases and therapeutic medications. 12 , 16 , 18 , 25 Age, sex, dementia, and presence of a roommate have been reported as risk factors for non-adherence. 12 , 18 , 21 In our study, we newly analyzed the number of medications to be discontinued before surgery and the number of days between the pharmacist interview and surgery as risk factors for non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Although approximately 4% of overall global deaths of T2DM occur, more than 80% of mortality occurs in the low-and middle-income countries (LMICs) [7,8]. Additionally, the management of this chronic metabolic disease incurs remarkable a burden due to its diverse complications and outcomes largely attributed to non-adherence to anti-diabetic medications that remain a concern [9,10]. The World Health Organization (WHO) projected that by 2040, 8.5% of the world's population (more than 642 million patients with diabetes) will have T2DM in comparison to 4.7% in 1980s [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…More, high cost of antidiabetic drugs, long duration of taking medications, side effects of anti-diabetic drugs such as fatigue, nausea, vomiting, psychological problems and itching, socio-cultural issues, substance use, health literacy, belief, availability and affordability of insulin, and non-persistence are factors of non-adherence [7,39,40]. Previous studies identified factors of non-adherence such as poorer treatment outcomes, low demographic characteristics (like young age, lower education and income), progression of disease symptoms and complications [10,28]. Optimal glucose control can be achieved through strict compliance to medications, diet, and lifestyle modifications, which in turn minimize long-term complications [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…with mediating improvements in diabetes clinical outcomes in patient-only interventions. 40,41 However, in this trial, improvements in cardiac risk score and individual physiological outcomes were similar in both arms.…”
Section: Discussionmentioning
confidence: 67%